Integrity and Internal Control in Information Systems Strategic Views on the Need for Control - van Biene-Hershey, Margaret E.; Strous, Leon A.M (IFIP Advances in Information and Communication Technology, 2000)
This publication is a collection of papers from the Third International Working Conference of IFIP TC-11 Working group 11.5 on "Integrity and Internal Control in Information systems". IFIP TC-11 Working Group 11.5 explores the area of integrity within information systems and the relationship between integrity in information systems and the overall internal control systems that are established in organizations to support the corporate governance codes. We want to recommend this book to security specialists, IT auditors and researchers who want to learn more about the business concerns related to integrity. Those same security specialists, IT auditors and researchers will also value this book for the papers presenting research into new techniques and methods for obtaining the desired level of integrity. The third conference represents a continuation of the dialogue between information security specialists, internal control specialists and the business community. The conference objectives are: • To present methods and techniques that will help business achieve the desired level of integrity in information systems and data; • To present the results of research that may in future be used to increase the level of integrity or help management maintain the desired level of integrity; • To investigate the shortcomings in the technologies presently in use, shortcomings that require attention in order to protect the integrity of systems in general